Answer:
The answer is
Step-by-step explanation:
The sequence above is a geometric sequence
For an nth term in a geometric sequence
[tex]A(n) = a ({r})^{n - 1} [/tex]
where n is the number of terms
r is the common ratio
a is the first term
From the question
a = - 16
To find the common ratio divide the previous term by the next term
That's
r = 24/-16 = -3/2 or -36/24 = - 3/2
Since we are finding the 8th term
n = 8
Substitute the values into the above formula
That's
We have the final answer as
Hope this helps you